Sensitivity of functional targeted neuropeptide evaluation in testing pregabalin analgesic efficacy in a rat model of osteoarthritis pain. (23rd May 2019) - Otis, Colombe; Guillot, Martin; Moreau, Maxim; Pelletier, Jean‐Pierre; Beaudry, Francis; Troncy, Eric
Abstract: The monosodium iodoacetate (MIA)‐induced joint degeneration in rats is the most used animal model to screen analgesic drugs to alleviate osteoarthritis (OA) pain. This study aimed to evaluate the analgesic efficacy of pregabalin (PGB) in an MIA‐induced OA model in rodents by using functional and neuroproteomic pain assessment methods. Treatment group included PGB in curative intent over 9 days compared to gold standard therapy (positive controls) and placebo (negative control). Functional assessments of pain (quantitative sensory testing and operant test) were performed concomitantly with spinal neuropeptides quantification. At day 21 post‐OA induction, PGB in MIA rats reduced tactile allodynia ( P  =   0.028) and improved the place escape/avoidance behaviour ( P  =   0.04) compared to values recorded at last time‐point before initiating analgesic therapy. All spinal neuropeptide concentrations, such as substance P, calcitonin gene‐related peptide, bradykinin and somatostatin, came back to normal (non‐affected) rat values, compared to their increase observed in MIA rats receiving the placebo ( P  <   0.0001). Initiated 13 days after chemical OA induction, repeated medication with PGB provided analgesia according to quantitative sensory testing, operant test and targeted neuropeptides pain assessment methods. This report highlights the interest of using reliable and sensitive methods like targeted neuropeptide quantification to detect the analgesic effects of a test article with concomitant functional assessments of pain when studying OA pain components.